2022
DOI: 10.3389/fpsyg.2022.833776
|View full text |Cite
|
Sign up to set email alerts
|

The Benefits of Being Proactive While Working Remotely: Leveraging Self-Leadership and Job Crafting to Achieve Higher Work Engagement and Task Significance

Abstract: Given the growing number of remote and hybrid working arrangements, this research investigates the process and outcomes of proactivity during remote work. We approach proactivity during remote working as a resource-building process and integrate self-leadership and job crafting literature. We propose that employees’ self-leadership allows them to regulate their resources optimally, enabling resource availability that can be used to arrange remote working demands and resources proactively. We collected three-wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 62 publications
(115 reference statements)
0
9
1
Order By: Relevance
“…First, our results substantiate our claim about how positive leadership can potentiate followers' self-leadership, particularly for those employees working in remote settings. A detailed inspection of the recent empirical self-leadership studies reviewed shows that from all self-leadership behavior-focused strategies (Manz, 1986;Neck and Houghton, 2006), self goal-setting was the most consistent predictor of positive outcomes in remote work settings (Müller and Niessen, 2019;Costantini and Weintraub, 2022;Sjöblom et al, 2022). However, in our laboratory experiment emulating a remote work scenario study, we did not find a main effect of self-set goals on task performancerelated outcomes.…”
Section: Theoretical Implicationscontrasting
confidence: 66%
See 1 more Smart Citation
“…First, our results substantiate our claim about how positive leadership can potentiate followers' self-leadership, particularly for those employees working in remote settings. A detailed inspection of the recent empirical self-leadership studies reviewed shows that from all self-leadership behavior-focused strategies (Manz, 1986;Neck and Houghton, 2006), self goal-setting was the most consistent predictor of positive outcomes in remote work settings (Müller and Niessen, 2019;Costantini and Weintraub, 2022;Sjöblom et al, 2022). However, in our laboratory experiment emulating a remote work scenario study, we did not find a main effect of self-set goals on task performancerelated outcomes.…”
Section: Theoretical Implicationscontrasting
confidence: 66%
“…Müller and Niessen (2019) reported that part-time teleworkers selfset goals more often while working remotely than when working in the office, which increased their work satisfaction. Similarly, Costantini and Weintraub (2022) reported that self-setting goals and self-rewarding strategies elicited job crafting and increased work engagement when working from home. Finally, self-set goals predicted remote workers' job meaningfulness and negatively predicted burnout (Sjöblom et al, 2022).…”
Section: Interactive Effects Of Goal Setting Types and Leadership Sty...mentioning
confidence: 97%
“…The unexpected outbreak of the COVID-19 pandemic in 2020 and its rapid spread around the world have brought radical changes to work life, dramatically impacting the workplaces across the globe (Kniffin et al, 2021;Wang et al, 2021). Of these numerous changes, perhaps the most remarkable was the widespread, almost overnight switch to mandatory and full-time remote work, a transition which has created thoroughgoing challenges for employees as well as organizations (Chong et al, 2020;Costantini and Weintraub, 2022). In this new and unfamiliar context, employees have found themselves applying different behavioral and cognitive self-management strategies to cope with the challenges associated with remote work.…”
Section: Introductionmentioning
confidence: 99%
“…The growth of physically distant working conditions (e.g., telework or hybrid work), which has resulted in greater flexibility and autonomy in daily working routines (Müller and Niessen, 2019), necessitates further investigation of the effects of self-leadership in such work contexts. Surprisingly, few attempts (Castellano et al, 2021;Costantini and Weintraub, 2022) have been made to evaluate the outcomes of self-leadership in remote or hybrid working contexts, which might in fact serve as ideal settings to study the effects of "leading oneself " toward task accomplishment (Manz, 1986). Although previous research has demonstrated a link between self-leadership and employee performance in remote work settings (Castellano et al, 2021;Costantini and Weintraub, 2022), these studies focused on a single aspect of work role performance, i.e., task performance or proactivity, among remote workers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation